The 16th international symposium on critical care and emergency medicine 2009 - Chew Keng, Sheng (Pusat Pengajian Sains Perubatan, 2009)
The practice of allowing family members to witness on·goh')gilc:tiye resuscitation has been gaining grounds in many .9evelop~d cquntries since-tfWiSfirit introduced in the early 1990s.ln many Asian countries, the acceptability of ~~~has not been ~~- .. Methods ' ' This Is the ptehrniriary flnll[ng '_!>nn!>ngoirijf \i!lliiil~IY; s~")llj~ded selfadrtliniStered questionnaire ~y frorn l'loVernber 2008 tO NOveoil~f 2IJ09 to look into theilltitua.es of heatthdire~ti>wiltds.a!IOwi~filrnil~ ptiosl!iice l.l'llrlng·resuscltation .. _ ;t=f~~~~~~~t,w;:<?JT~~~·~~~~ergency rnp~J .. ~!II\1UP to. 36 responders or 83.7%1 Perf!·> " ".· .f. i n~·~i9f._PI'PI'S rituals Qr·n.·te._ s, .including.. prayer a.nd ab~ !h..W. ~--iA<Ilvklllal ~ur~ oilost ~mat on~, pjood,otal~ng. sellin~if!travenous cannula should pe. abo wed to be Wit~essed. conclusiOn The.«>nceptofailoWingf•rniiV presence Is not well accepted by our !taffs although most of them agree that they have a right to be around.